2006
DOI: 10.1891/rtnp.20.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating the Strangeren Casa:How Mexican American Elders and Caregivers Decide to Use Formal Care

Abstract: Mexican American elders have higher levels of functional impairment and chronic illness, yet they use formal home care services less than do non-Hispanic White elders. This article describes the processes by which Mexican American elders and their caregivers decide to use home care services. Interviews were conducted with Mexican American elders (n = 11) and family caregivers (n = 12) for a sample of 23 individuals. The emerging substantive grounded theory included three stages that described the process of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…Such an intervention could also address elders’ and caregivers’ confidence in HCS. An earlier study that found that the process of deciding to use HCS was initiated by the caregiver in MA families (Crist, García-Smith, & Phillips, 2006). The fact that caregivers’ but not elders’ responses about Service Awareness were significant demonstrates that elders may need more understanding about HCS, and that caregivers’ awareness about service currently is the key to the use of HCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an intervention could also address elders’ and caregivers’ confidence in HCS. An earlier study that found that the process of deciding to use HCS was initiated by the caregiver in MA families (Crist, García-Smith, & Phillips, 2006). The fact that caregivers’ but not elders’ responses about Service Awareness were significant demonstrates that elders may need more understanding about HCS, and that caregivers’ awareness about service currently is the key to the use of HCS.…”
Section: Discussionmentioning
confidence: 99%
“…Use of HCS prevents the onset of acute illness, controls acute illness episodes, and helps manage chronic conditions (Anderson & Horvath, 2002). Recent studies revealed that use of HCS among MA elders is a complex phenomenon that includes caregivers’ perspectives (Crist, García-Smith, & Phillips, 2006). To date, no theory has captured this complexity.…”
mentioning
confidence: 99%
“…In this exemplar, various methodologies included ethnography, already briefly described, 6 grounded theory, 14 and model testing. 15 Obviously, retroduction , going back to the community and conducting exploratory qualitative research when more quantitative studies made apparent the need for conceptual exploration and development, was sometimes appropriate.…”
Section: The Pragmatic Approach With Vulnerable Populationsmentioning
confidence: 99%
“…Caregivers’ and elders’ social processes shaped families’ overt and covert negotiations about elder care management. 14 Families together negotiated their decision to seek information about home care services, initiating a shift in the family’s level of confidence and trust toward bringing “a stranger” (home care services staff) into the home. Elders eventually accommodated by coming to think of home care services staff as kin, using the culturally specific personalismo (Mexican American priority of establishing a personal relationship over the Anglo focus on a professional relationship).…”
Section: The Pragmatic Approach With Vulnerable Populationsmentioning
confidence: 99%
“…Mexican-origin elders also tend to underutilize formal caregiving services (Crist, Garcıa-Smith, & Phillips, 2006; A. P. Herrera, Benson, Angel, Markides, & Torres-Gil, 2013), including nursing homes and other long-term private-pay care facilities, even when they suffer a significant decline in functional capacity (Espino, Angel, Wood, Finely, & Ye, 2013).…”
Section: Introductionmentioning
confidence: 99%